THE INFLUENCE OF COMPETITION IN THE GROWTH-CLIMATE RELATIONSHIP OF Pinus taeda: A CASE STUDY IN SOUTHERN BRAZIL - Schons, Cristine Tagliapietra; Costa, Emanuel Arnoni; Finger, César Augusto Guimarães (Floresta, 2019)
Understanding how climate affects tree growth is crucial for assessing climate change impacts on forests. Furthermore, trees in more competitive environments appear to respond to climate differently than trees in less competitive environments. An important tool for investigating the growth-environment relationships is tree ring dating. This study aimed to characterize the climatic factors that affect Pinus taeda growth in southern Brazil in two distinct stand types: open growth trees and competing trees. We hypothesized that competing trees present more vulnerable responses to climate variability than open growth trees. Thus, we used increment borers to access long-term growth through tree rings. Pearson’s correlation was applied to compare radial growth with monthly and annual climatic data. The chronologies generated for the two environments present similar year-to-year growth patterns. However, competing trees are more sensitive under limiting climate conditions than open growth trees. Water availability during the current spring/summer was the primary climate constraint for P. taeda growth in the region, followed by high temperatures during the summer, probably due to photosynthetic restrictions. The paper provides additional information on climatic factors that contribute to growth models and reports an important research field, considering planning forest management in the future.